Extreme solar storms and the quest for exact dating with radiocarbon - Heaton, TJ; Bard, E; Bayliss, A; Blaauw, M; Ramsey, CB; Reimer, PJ; Turney, CSM; Usoskin , I (Springer Nature, 2024)
Radiocarbon (14C) is essential for creating chronologies to study the timings and drivers of pivotal events in human history and the Earth system over the past 55,000 years. It is also a fundamental proxy for investigating solar processes, including the potential of the Sun for extreme activity. Until now, fluctuations in past atmospheric 14C levels have limited the dating precision possible using radiocarbon. However, the discovery of solar super-storms known as extreme solar particle events (ESPEs) has driven a series of advances with the potential to transform the calendar-age precision of radiocarbon dating. Organic materials containing unique 14C ESPE signatures can now be dated to annual precision. In parallel, the search for further storms using high-precision annual 14C measurements has revealed fine-scaled variations that can be used to improve calendar-age precision, even in periods that lack ESPEs. Furthermore, the newly identified 14C fluctuations provide unprecedented insight into solar variability and the carbon cycle. Here, we review the current state of knowledge and share our insights into these rapidly developing, diverse research fields. We identify links between radiocarbon, archaeology, solar physics and Earth science to stimulate transdisciplinary collaboration, and we propose how researchers can take advantage of these recent developments.